The effect of carbon insoles on left and right balance in cycling - Koch, M.; Fröhlich, M.; Weiler, B.; Emrich, E.; Urhausen, A. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: In cycling, athletes with a more or less asymmetric body structure intend to move the crank-set on a symmetric bike with a set and fixed positioning of saddle, handlebar and pedals. To compensate the body`s asymmetry, cyclists actively adapt their movement to the static bike, which could lead to overuse injuries and reduced power output. Special insole devices made of carbon are expected to influence the biomechanical structures of the foot and the linked body parts such as leg, hip, and spine in such a way that asymmetries are reduced (Jeukendrup & Martin, 2001). Hence, by using the insole devices, the power output should be higher in total and the power of the left and right leg should be more balanced (Schmidt et al., 2011). Methods: The effects of cycling-specific carbon insoles were evaluated with respect to their impact on the lateral difference of the left and right leg during a steady-state test with sub-maximal load and in an isokinetic maximum test. 8 male cyclists and 2 male triathletes (age: 26.2 ± 5.6 years, height: 181.0 ± 5.1 cm, mass: 76.6 ± 4.4 kg, foot length 28.3 ± 1.0 cm, mean power in test: 804.1 ± 114.6 Watt) at least at national level were tested twice for lateral difference in a randomized blind application regarding (a) mean power, (b) tangential force, and (c) efficiency during 30 s at 280W steady-state resistance with randomized application of a standard insole or the cycling-specific carbon insole. The same parameters were measured twice during a 20 s isokinetic maximum test. Results: There was no general significant difference in all tests between the carbon insole and the standard insole. The lateral power difference was reduced from 19.3 ± 15.4% with standard insoles to 18.2 ± 10.7% in the submaximal test and from 11.5 ± 6.4% to 10.4 ± 4.2% in the isokinetic max test. Additionally, the tangential force difference between the left and right leg was reduced in both subtests with 1% (sub-maximal) and 0.2% (isokinetic max test), respectively. Meanwhile, the lateral difference of the efficiency increased from 11.5 ± 10.3% to 11.7 ± 11.3% in the sub-maximal test and from 4.2 ± 4.1% to 4.6 ± 3.7% in isokinetic max test. Discussion: At an individual level, the cycling-specific carbon insoles show partly positive effects in terms of three parameters, however, the overall result is not conclusive.